Social Conflict, Security and Peace Building in the Information Communication Age (Global Journal of Human-Social Science, 2013)
The paper was burdened by the need to evolve a proactive use of the media and information communication technology (ICT) as instruments for peace building, security and conflict management system (CMS) and how these can be realised. Looking at ICT and how it affect security and security soft and hard wares. It also considered ICT as a driver of social conflict and security. The paper saw peace building as a product of ICT and how Information system management (ISM) can either increase or decrease conflict eruption.
Keywords: social conflict; ISM; ICT; peace building; CMS; security